Peningkatan Potensi Wisata Umbulan Desa Jajar Melalui Pendampingan Pengelolaan Ekowisata Berbasis Industri Kreatif Desa Wisata Kabupaten Trenggalek - Wahyu Nugroho; Faridatul Afidah; Mohamad Nurafan Kudori; Titis Faseh Leviliano; Huzein Ridho Prasojo; Afida Anindya; Ardhika Aulia Agoestin (Abdimas Universal, 2023)
Empowerment of tourism potential Umbulan Jajar Village through ecotourism Management Assistance based on Creative Industries towards 100 tourism villages Trenggalek Regency is a capacity building program organized by the Ministry of education and culture through the Student Executive Board STKIP Pgri Trenggalek with Field Assistant Lecturers to optimize the tourism potential of Umbulan Karang. Umbulan Karang is a gift of natural beauty located in Jajar Village, Gandusari District, Trenggalek Regency. Umbulan tourism has been used as Jamcab / raimuna Scout activities throughout Trenggalek Regency, so it has the potential to be developed as a camping ground and outbound area while maintaining the existing local wisdom. However, this Umbulan tour began to recede in operation with restrictions in everything during Covid-19, making this tour not operational until now. The establishment of the social media management team of Desa Wisata (Community Based Tourism) is one of the main attractions in desa Jajar. A combination of smart digital strategies and active participation of local communities, Umbulan Tourism Village managed to effectively promote itself, increase tourist awareness, and form the basis of sustainable growth in local tourism to succeed the Trenggalek Regency 100 tourism villages program.